Subrogation as a Legal Protection Mechanism for Banks in Kredit Usaha Rakyat (KUR) Guarantee Schemes - Raditya Maharani; Firdausi, Kamalia; M. Dju Bire, Chatryen (Program Studi Hukum Keluarga Islam Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines how subrogation functions within the Credit Guarantee mechanism of a government-backed microcredit program in Indonesia (Kredit Usaha Rakyat) as a tool for protecting banks’ legal interests in cases of non-performing loans. Although subrogation is formally regulated under the Indonesian Civil Code, the practice of KUR credit guarantees demonstrates that subrogation is often narrowly understood as merely an administrative consequence of guarantee claim payments. This situation arises because KUR guarantees cover only a portion of the credit risk, resulting in a partial transfer of receivables and creating legal complexities in the relationships among banks, debtors, and credit guarantee institutions. Using a normative legal research approach through the examination of the Indonesian Civil Code, regulations governing the KUR program guarantee scheme, and the prudential principle in banking law, this study finds that subrogation in KUR guarantees is inherently partial and possesses a strategic function that has not yet been fully optimized. Partial subrogation not only facilitates the transfer of receivables but also serves as a proportional and layered legal protection mechanism for banks in resolving non-performing loans. This study emphasizes that the systematic integration of subrogation within the legal framework of a government-backed microcredit program in Indonesia (Kredit Usaha Rakyat) guarantee scheme has the potential to strengthen the legal protection of banks’ interests while supporting the stability of government- backed credit distribution. Keywords: Subrogation; KUR; Credit Guarantee; Legal Protection of Banks.